Creativity, Entrepreneurship Education, Self-Efficacy, dan Income Expectations Terhadap Interest In Entrepreneurship - Ratna Wijayanti; Nabila Nastri Ekarunia; Desy wulandari; Wahab Wahab; Eko Prawoto (MANAJEMEN, 2026)
Unemployment is a persistent problem in developing countries. This problem arises from an imbalance between the number of workers needed and the number of available jobs. This study aims to demonstrate the influence of Creativity, Entrepreneurship Education, Self-Efficacy, and Income Expectations on Interest in Entrepreneurship among FEB students from the 2021 intake of Al-Qur'an Science University in Wonosobo. The method applied in this study is a quantitative method, with the analysis technique used is multiple linear regression. The population in this study were FEB students from the 2021 intake of Al-Qur'an Science University in Wonosobo. The sample consisted of 100 respondents selected through simple random sampling. The Adjusted R Square test results showed a value of 50.6%, while 49.4% was due to other factors. The analysis shows that Creativity, Entrepreneurship Education, Self-Efficacy, and Income Expectations have a positive and significant effect on students' interest in entrepreneurship, emphasizing the importance of strengthening these factors to encourage entrepreneurial interest. The suggestion in this research is to further improve entrepreneurship training or practice for students.